Pattern of Pediatric Tuberculosis: A Study at Tertiary Care Hospital (Medical Forum Monthly, 2024)
Objective: To determine the patterns of pediatric tuberculosis at tertiary level hospital.Study Design: Descriptive / cross sectional study.Place and Duration of Study: This study was conducted at the Department of Pediatric MTI Hayatabad Medical Complex/Khyber Girls Medical College, Peshawar from January 2018 to September 2018.Materials and Methods: The study duration was 8 months and a total of 57 patients were included in the study, which fulfilled the inclusion criteria. PPA scoring was used for the diagnosis. 95% confidence level and 7% margin of error using WHO software for sample size. The SPSS latest version was used to analyze the data. For categorical data frequencies and % ages were calculated and the data was presented in tabulated form.Results: In this study 57 patients with diagnosis of pulmonary or extrapulmonary tuberculosis were included in the study. Male patients were 31 while female were 26 with male to female ration of 1.2:1. New Pulmonary tuberculosis cases were 41, 13 were new extrapulmonary cases while 2 were pulmonary relapse cases. Smear was made in 44 cases and only 13 were smear positive cases.Conclusion: Pediatric tuberculosis is one of the growing and leading concerns of our region. Pulmonary tuberculosis is still the most common type of pediatric tuberculosis.